Digitising a Turn-Based Strategy Board Game: Implementation of Spellcaster Using the Mini-Max Algorithm - Wang, Yukai (International Journal of Computer Science and Information Technology, 2024)
Spellcaster is a turn-based strategy board game for two players, involves players casting spells by making sequences of gestures, aiming to defeat their opponent through different kinds of spells within a turn-based system. The research succeeded in the implementation of Spellcaster as a 2-player game system, with an AI opponent who can make reasonable decisions. The digitised game is developed using the LibGDX game engine because of its cross-platform features and high editability; and implemented in the Java language, using java’s object-oriented features to improve programming efficiency. The game’s AI opponent is implemented using the Mini-Max ideas, with an evaluation function that focuses on the gesture selection of the current turn.